2020
DOI: 10.21608/bjas.2020.137582
|View full text |Cite
|
Sign up to set email alerts
|

Early Postoperative Arrhythmias after Paediatric Cardiac Surgery

Abstract: Pediatric arrhythmias represent around 55.1 per 100,000 patients assessed in pediatric crisis divisions. Patients with intrinsic coronary illness are at deep rooted hazard for the advancement of arrhythmias. The point of this investigation is to assess the rate and kinds of early postoperative arrhythmias after pediatric cardiovascular medical procedure. Strategies: The current investigation included 227 pediatric patients with intrinsic heart maladies made arrangements for careful repair.All patients will be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
(19 reference statements)
5
1
0
Order By: Relevance
“…The highest prevalence of CHB was found in the surgical VSD closure procedure, where out of five patients who experienced CHB, three (60%) patients had a surgical VSD procedure. This is consistent with previous studies, CHB is the most common complication after congenital heart defect surgery, 2–4,7,9 and it occurred 1%–6% after congenital heart defects surgery 16 . Atrioventricular node is found in a specific area called the triangle of Koch within the bottom part of the right atrium.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The highest prevalence of CHB was found in the surgical VSD closure procedure, where out of five patients who experienced CHB, three (60%) patients had a surgical VSD procedure. This is consistent with previous studies, CHB is the most common complication after congenital heart defect surgery, 2–4,7,9 and it occurred 1%–6% after congenital heart defects surgery 16 . Atrioventricular node is found in a specific area called the triangle of Koch within the bottom part of the right atrium.…”
Section: Discussionsupporting
confidence: 91%
“…3,10,20 Regarding the duration of Aortic Cross Clamp (AoX Time), this study found that the mean duration of AoX time was longer in the arrhythmia group, with 115.58 ± 34.38 min compared to the nonarrhythmia group with a mean of 73.59 ± 37.28 min, and it showed a significant difference with a p-value of .001. This result is in line with previous studies by Shalby et al, 7 Delaney et al, 9 and Alotaibi et al, 3 but it is not in line with the previous study by Sidra et al 2 Based on the duration of ischemia (ischemic Time), this study found that the mean duration of ischemic time in the arrhythmia group was longer, with 106.33 ± 30.63 min compared to the nonarrhythmia group with a mean of 65.43 ± 34.50 min, and it showed a significant difference with a p-value of .000. This result is in line with the previous study by Abdel Gawad et al 4 Based on the postoperative electrolyte levels, there were no statistically significant difference found between the arrhythmia and nonarrhythmia groups for sodium levels, while the potassium levels showed the opposite with a p-value of less than .05.…”
Section: Re Sultssupporting
confidence: 94%
See 3 more Smart Citations